AN IMPLICATIONS OF THE DEBTOR'S DEFAULT ON THE EXECUTION OF TWO-WHEEL MOTORCYCLES WITHOUT A FIDUCIARY GUARANTEE CERTIFICATE - Sanusi, Sanusi; Nuridin, Nuridin (UNISSULA, 2023)
This research aims to explain to the public regarding fiduciary issues as well as the consequences that the finance company will receive if it assigns a debt collector forcibly withdrawing two-wheeled motorized vehicles without a fiduciary guarantee deed. This paper uses normative legal research with a statutory regulatory approach (Statuta Opproach). The results of this research show that the execution of the fiduciary guarantee object cannot be carried out whether they have a fiduciary guarantee deed or not, except based on the debtor's voluntariness or based on a court decision which says that the debtor is in default, This is based on the decision of the Constitutional Court which said the sound of article 15 paragraph (2) of Law No. 42 of 1999 is unconstitutional.